Microbial transformation of PEG 400 by Pseudomonas stutzeri: implications for environmental remediation - Reyes-Bocanegra, Mijhail; Piundo-Ponce, Ever; Bello-Yupanqui, Fabian; Rojas-Villacorta, Walter (Frontiers in Microbiology, 2025)
Polyethylene glycol 400 (PEG 400) is a synthetic polymer that has found wide application in various industries. Despite its low toxicity, its persistence and mobility in aquatic ecosystems pose significant environmental risks. This study evaluated the ability of Pseudomonas stutzeri grow in minimal saline medium (MSM) using PEG 400 as the sole source of carbon and energy. Structural modifications of the polymer were analyzed by FTIR spectroscopy to assess its potential application in environmental remediation. Regarding methodology, the growth and the formation of clear zones were first evaluated in a solid medium supplemented with PEG 400. Subsequently, liquid medium systems were established in which the bacteria were inoculated and physicochemical parameters (pH, redox potential, and dissolved oxygen) and growth kinetics were monitored for a period of 30 days. The alterations and modifications in the structure were evaluated by means of FTIR spectroscopy. The temperature (28 °C) was maintained at a constant level throughout the evaluation period. The results demonstrated sustained bacterial proliferation in both systems (2% and 5%) across both solid and liquid media. Clear zones were observed in the solid medium. The growth rate (μ = 0.35 days−1) exhibited a higher value in the system with 2% PEG 400, while the 5% system demonstrated more stable proliferation. The pH levels of the systems remained within the slightly alkaline range (7.48–7.90). Fourier transform infrared spectroscopy (FTIR) analysis revealed structural alterations in the polymer at the conclusion of the treatment process. These alterations included the rupture of ether bonds and the subsequent formation of carbonyl groups. The findings highlight the potential of P. stutzeri to degrade synthetic polymers under laboratory conditions, supporting its application in bioremediation of contaminated water. The study also contributes to SDG 13 on climate action.